2007
DOI: 10.1098/rsif.2007.0223
|View full text |Cite
|
Sign up to set email alerts
|

Termites live in a material world: exploration of their ability to differentiate between food sources

Abstract: Drywood termites are able to assess wood size using vibratory signals, although the exact mechanism behind this assessment ability is not known. Important vibratory characteristics such as the modal frequencies of a wooden block depend on its geometry and boundary conditions; however, they are also dependent on the material characteristics of the block, such as mass, density and internal damping. We report here on choice experiments that tested the ability of the drywood termite Cryptotermes secundus to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The vibrations produced by foraging and feeding can also be used as signals. Drywood termites of the genus Cryptotermes choose optimal food sources based on the substrate-borne vibrations produced by their own activity, which are modulated by the size and the other properties of the wood upon which they are feeding (Evans et al 2005;Inta et al 2007). At the same time, they are attracted by vibrations produced by their nestmates, and thus the social cohesion of the colony is maintained as a result of the perception of passive signals produced by foraging and wood-chewing ).…”
Section: Other Functions Of Vibratory Communicationmentioning
confidence: 98%
“…The vibrations produced by foraging and feeding can also be used as signals. Drywood termites of the genus Cryptotermes choose optimal food sources based on the substrate-borne vibrations produced by their own activity, which are modulated by the size and the other properties of the wood upon which they are feeding (Evans et al 2005;Inta et al 2007). At the same time, they are attracted by vibrations produced by their nestmates, and thus the social cohesion of the colony is maintained as a result of the perception of passive signals produced by foraging and wood-chewing ).…”
Section: Other Functions Of Vibratory Communicationmentioning
confidence: 98%
“…The drywood termite has the ability to assess physical properties of the wood such as mass, density, and internal damping [23] through the reception of vibratory signals [24]. Indrayani et al [25] also observed that I. minor touches the surface of the timber with its antennae before penetrating the timber by engaging in cutting, pulling, and collecting activities.…”
Section: Nest-site Selectionmentioning
confidence: 98%
“…This is a chance for their early detection. This can be explained by the working modus of termites (Evans et al 2005Inta et al 2007) as they send vibration signals to determine the wood Brought to you by | UCL -University College London Authenticated Download Date | 4/24/17 10:06 AM thickness. Though the vibratory characteristics of materials are strongly dependent on its properties (Thomson 1993), the termites are able to cope with these different parameters.…”
Section: Foraging Characteristicsmentioning
confidence: 99%